Whole-body cryostimulation exposures effectively alleviates menstrual-related pain and associated sleep disturbances in young women: a randomized controlled trial - Bretonneau, Quentin; Arc-Chagnaud, Coralie; Dugué, Benoit; Dupuy, Olivier; Delpech, Nathalie; Enea, Carina; Bosquet, Laurent (Frontiers in Pain Research, 2025)
IntroductionMenstrual-related pain and sleep disturbances are widespread in women experiencing premenstrual syndrome and primary dysmenorrhea. Such disturbances could be alleviated through repeated whole-body cryostimulation (WBC) sessions. Therefore, this study aimed to assess the effect of menstrual-related pain on sleep parameters, and the impact of WBC exposures on pain and sleep.Materials and methodsPain and sleep were evaluated for two 5-day periods under different conditions (control vs. WBC), randomly assigned across two consecutive menstrual cycles. Measurements began when the first pain/symptom indicating the onset of the menstrual phase was experienced. Pain was rated using a scale, while sleep was assessed using accelerometers and questionnaires. Throughout the 5-day WBC exposure, women underwent 3-min exposure to intense ventilated cold air each evening. After data collection, participants were categorized into high (HP) or low/no pain (LP) groups based on control pain scores.ResultsTwenty-nine naturally menstruating women were assessed. Perceived sleep quality was lower in the HP group compared to the LP group during the control condition (Spiegel score: 20.1 ± 2.3 vs. 22.3 ± 1.9, respectively; Cohen's d = 1.1). Across both groups, perceived sleep quality improved with the number of WBC exposures (night1: 19.5 ± 3.2 vs. night5: 23.5 ± 3.8; Hedge's g = 1.10). In the HP group, pain was reduced in the WBC condition compared to the control condition. Changes in pain and perceived sleep quality following WBC were correlated (r = −0.86).DiscussionWomen experiencing higher menstrual-related pain reported poorer perceived sleep quality. Their pain was reduced by WBC exposures. This improvement was highly associated with the enhancement in sleep quality.